Double Trouble Post-Femoral Fracture – A Rare Case Report - Haniza, Sahdi; Mohamad Zaki, Mohd Amin; Lee, Denis Dian; Ting, Cassandra (Radiance Research Academy, 2021)
been discussed extensively. Nevertheless, the simultaneous manifestation of FES and ACS after a single long bone fracture has never been reported. FES results from the extensive inflammatory response to fat emboli in the systemic microcirculation. The diagnosis is made with a set of specific clinical criteria. Treatment of FES is supportive. ACS ensues when a closed Osseofascial compartmental pressure exceeds the capillary perfusion pressure, leading to microvascular compromise. Fasciotomy is the only proven mode of treatment. We present a case of an 18 year-old-gentleman with closed traumatic femoral fracture, who then developed tense swelling of the ipsilateral thigh, Type I respiratory failure and axillary petechiae. A diagnosis of concurrent fat embolism syndrome and acute compartment syndrome of the thigh was made. High index of suspicion is essential for prompt diagnosis of concurrent FES and compartment syndrome as multiple complications that arise can be overlooked by unsuspecting practitioners who may be sidetracked by the multitude of presentations.